STEROIDS IV IODOKETONES A METHOD FOR THE CONVERSION OF ALL OSTEROIDSINTOI 4 3 KETOSTEROIDS - ROSENKRANZ, G; MANCERA, O; GATICA, J; DJERASSI, CARL (LABORATORIOS SYNTEX, CD. MEXICO, DF, MEX, 1950)
2-Bromo-3-ketoallosteroids, in contrast to 4-bromo-3-keto;;teroids of the normal series, react readily with sodium iodide in acetone solution to afford the corresponding 2-iodo ketones. When refluxed with Î³-collidine, deiodination occurs and the saturate
J ULTRASTRUCT RES
Keywords: STEROIDS, IODOKETONES, METHOD, CONVERSION, OSTEROIDSINTOI 4 3, KETOSTEROIDS; QUIMICA; QUIMICA ORGANICA; HIDROCARBUROS AROMATICOS